Scale and diversity of the physical technosphere: A geological perspective. (April 2017) - Zalasiewicz, Jan; Williams, Mark; Waters, Colin N; Barnosky, Anthony D; Palmesino, John; Rönnskog, Ann-Sofi; Edgeworth, Matt; Neal, Cath; Cearreta, Alejandro; Ellis, Erle C; Grinevald, Jacques; Haff, Peter; et al.
We assess the scale and extent of the physical technosphere, defined here as the summed material output of the contemporary human enterprise. It includes active urban, agricultural and marine components, used to sustain energy and material flow for current human life, and a growing residue layer, currently only in small part recycled back into the active component. Preliminary estimates suggest a technosphere mass of approximately 30 trillion tonnes (Tt), which helps support a human biomass that, despite recent growth, is 5 orders of magnitude smaller. The physical technosphere includes a large, rapidly growing diversity of complex objects that are potential trace fossils or 'technofossils'. If assessed on palaeontological criteria, technofossil diversity already exceeds known estimates of biological diversity as measured by richness, far exceeds recognized fossil diversity, and may exceed total biological diversity through Earth's history. The rapid transformation of much of Earth's surface mass into the technosphere and its myriad components underscores the novelty of the current planetary transformation.